Evaluation and Optimization of Cooling System for Generator and Bearing at Cirata Hydroelectric Power Plant - Hariyanto Hariyanto; Ary Bachtiar (Institut Teknologi Sepuluh Nopember, 2019)
Cirata hydroelectric is located in Purwakarta district, West Java, Indonesia. The cooling system is one of the main equipment in the hydroelectric generator that serves to cool the generator and bearing. In recent years, water quality has been a decreased in Cirata dam causing high levels of corrosion rate and abrasion of piping and heat exchanger equipment. Currently, the modification of the cooling system from open loop into closed loop at unit 1 has occurred. This study aims to optimize the closed loop cooling system in order to be able to serve all heat exchangers with better heat effectiveness and low cost. Second, it aims to evaluate the closed loop cooling system before and after optimization. The optimization analysis of the closed loop system was conducted by means of redesigning the shell and tube heat exchangers by referring to TEMA standards through tube diameter variations (1/2